Burden of Obstetric Fistula on the Rohingya Community in Cox's Bazar, Bangladesh - Mahmood, Iftikher; Biswas, Nrinmoy; Akter, Fahmida; Hansing, Johanna; Mahmood, Arman; Pugh, Ashley; Love, Jessica; Arrowsmith, Steven (Nepal Journal of Obstetrics and Gynaecology, 2018)
Since August 2017, a massive influx of over 800,000 Rohingya refugees have arrived in Cox’s Bazar, Bangladesh. The Rohingya state is one the poorest states in Myanmar, with ghetto-like camps and a lack of basic services and opportunities. In 1982, a new citizenship law was passed, effectively rendering the Rohingya stateless. As a result of this law, their rights to access health services have been restricted. Now, many Rohingya are living in Cox’s Bazar in tent-based refugee camps under extremely poor conditions without access to proper medical care, hygiene, sanitation, food or education. Lack of proper maternal health care, together with early marriage, malnutrition, poverty and the physical characteristics of the women in this community (small body shapes), exposes Rohingya women to a very dangerous position with high chances of developing obstetric fistula during childbirth. HOPE Hospital provides clinical care for women affected with obstetric fistula and is the only provider and referral center of fistula care in the region. Since the influx began, many fistula repairs have been carried out on Rohingya women at HOPE Hospital. This paper looks at fistula care and the psychosocial impact of fistula on victims in the refugee population, amid a massive humanitarian crisis.